FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PENYAKIT DERMATITIS ALERGIKA BERDASARKAN RISKESDAS DI INDONESIA 2007 - Pracoyo, Noer Endah (Prosiding Seminar Biologi, 2013)
National InstIitute of Health Research and Development has done the basic health during or ?Riskesdas in 2007?. The sample of ? Riskesdas ?  followed ? Susenas KOR? frame work. The objective of this research is to measure the proportion of arthritis in rural and urban area, the linkage between age, sex, occupation, welfare level, with the access of health services, towards arthritis in Indonesia. ?Riskesdas? 2007 designated a cross sectional, which descriptive design. The Population of ?Riskesdas? 2007 are households in all areas of the Republic of Indonesia which include province, regency, village. The data are taken from ?Riskesdas ? which have been cleaned and analyzed by univariate, bivariate, multivariate analysis. The results of study showed that 5 ( five ) of 6 ( six ) variables were statistically significant correlated those are residential area ( OR= 0,81 ; CI = 0,78 - 0,82 ), sex ( OR = 0,90 ; CI = 0,89 - 0,92 ), educational level (OR =  2,15  ;CI = 2,13 - 2,18 ), occupation (OR = 0,91 ; CI = 0,90 - 0,93 ), Health service  reach (OR = 0,95 ; CI = 0,94 -  0,96 ) while economic status (OR = 0,99 ; CI = 0 ,98 ? 1,0 )  is not significant  Key Words : Dermatitis allergic